2017
DOI: 10.1186/s12940-017-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-term air pollution exposure decreases lung function: a repeated measures study in healthy adults

Abstract: BackgroundDaily changes in ambient concentrations of particulate matter, nitrogen oxides and ozone are associated with increased cardiopulmonary morbidity and mortality, with the lungs and their function being a vulnerable target.MethodsTo evaluate the association between daily changes in air pollution and lung function in healthy adults we obtained annual lung function measurements from a routine worker health surveillance program not designed for research purposes. Forced Vital Capacity (FVC), Forced Expirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 24 publications
5
25
2
1
Order By: Relevance
“…Epidemiological studies indicated that daily changes in ambient concentrations of NO 2 and SO 2 trigger negative health effects on cardiopulmonary function, with both long-term and short-term exposure being associated with mortality risk (Brunekreef et al 2009 ; Ghozikali et al 2015 ; Int Panis et al 2017 ; Miri et al 2016 ). Our study found a relationship between lung cancer mortality and elevated SO 2 level.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies indicated that daily changes in ambient concentrations of NO 2 and SO 2 trigger negative health effects on cardiopulmonary function, with both long-term and short-term exposure being associated with mortality risk (Brunekreef et al 2009 ; Ghozikali et al 2015 ; Int Panis et al 2017 ; Miri et al 2016 ). Our study found a relationship between lung cancer mortality and elevated SO 2 level.…”
Section: Discussionmentioning
confidence: 99%
“…One study assessed the relationship between acute exposure to PM 10 and observed a significant change in FEV 1 of −15.8 mL (95% CI −21.9 to −9.6) per 10 µg/m 3 increase in PM 2.5 . 43 Three studies assessed the relationship between acute exposure to PM 10 and absolute difference in FEV 1 . 25 38 40 A random effects model yielded a pooled estimate of absolute difference in FEV 1 of 0.05 mL (95% CI −0.10 to 0.20) associated with 10 µg/m 3 increase in exposure to PM 10 (figure 2B).…”
Section: The Association Between Acute Exposure To Outdoor Particulatmentioning
confidence: 99%
“…A study of lung function in response to daily measures of air pollutants was carried out in Belgium. 93 Several repeated measures of lung function were obtained from 2449 adults over a 4-year period between 2011 and 2015. No significant association was observed for O3, but several measures of lung function decreased in response to elevated concentrations of PM10 and NO2 in the days prior to testing.…”
Section: Overview Of Recent Human Health Studiesmentioning
confidence: 99%